Kolaborasi Digital dalam Pengembangan Sanjai Minang di Era E-Commerce pada Kabupaten limapuluh Kota - Raini, Putri; Annas, Firdaus; Tiwi, Tiwi; Okra, Riri (JOVISHE : Journal of Visionary Sharia Economy, 2023)
This research aims to design a digital collaboration hub in order to support the development of typical West Sumatran culinary products, especially sanjai minang, and introduce Aceh Coffee in the ICommerce era. Sanjai Minang, as one of the typical culinary products originating from Limapuluh kota district, has great potential to develop and introduce the distinctive taste of Minangkabau to a wider market, both domestically and internationally. On the other hand, Aceh coffee is also known for its high quality and rich flavours, which can compete in the global market. However, the biggest challenge faced by businesses of both products is the lack of access to wider markets and limitations in utilising digital technology. Therefore, this research proposes a digital collaboration hub platform that integrates various parties such as culinary entrepreneurs. By using the Research and Development (R&D) approach. The R&D method used consists of five main stages: (1) problem identification and product development potential, (2) digital hub design involving various features to support collaboration, marketing, and distribution, (3) hub prototype development, (4) implementation and field trials, and (5) evaluation and continuous improvement. It is expected that the results of this research can provide significant contributions to the development of typical Sumatran culinary products through the use of digital platforms integrated with the ICommerce ecosystem, while increasing the competitiveness of local products in the global market.